Thermal Study of a one-meter long Neon Cryogenic Pulsating Heat Pipe. (April 2019) - Barba, M; Bruce, R; Bouchet, F; Bonelli, A; Baudouy, B
Abstract: Cryogenic Pulsating Heat Pipes (PHP) are excellent candidates for cooling superconducting magnets due to their lightness, simple configuration and thermal performance. Long cryogenic PHP using Neon as working fluid have been developed and are under consideration to be used as thermal links between a superconducting magnet (the hot source) and a cryocooler (the cold source) maintaining the latter out of the influence of the magnetic field. Tests in a horizontal 1 m long PHP composed of 36 parallel tubes have been performed. Using Neon as working fluid, the device shows high performance, even though the inner diameter of the tubes (1.5 mm) is larger than the critical diameter determined by the most commonly accepted criterion in the literature. During the tests, the condenser temperature was maintained at 27 K while the heat load was increased gradually at the evaporator part. The PHP was able to transfer a heat load of 50 W from the evaporator to the condenser with an equivalent thermal conductivity of 70 kW/mK.